Strategies for Delivering Islamic Da'wah Through Islamic Music in the Digital Era to Increase the Religious Motivation of Islamic Students - Yogi Setiawan; Masripah; Asep Tutun Usman (al-Afkar, Journal For Islamic Studies, 2026)
This research is motivated by the need for more creative and relevant da’wah methods in accordance with contemporary developments, particularly for the younger generation in Islamic boarding schools. This study aims to analyze the da’wah delivery strategies through Islamic musical arts and their role in enhancing students’ religious motivation at Al-Muawanah Islamic Boarding School, Rancabango, Garut. The study employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects included the head of the Islamic boarding school, Islamic music instructors, and students involved in hadrah and marawis activities. Data were analyzed using triangulation techniques to ensure the validity of the findings. The results indicate that the da’wah strategy through Islamic musical arts is implemented by integrating Islamic values into song lyrics, training activities, and performances. Islamic musical arts function as an effective medium of da’wah because they attract students’ interest, touch emotional and spiritual aspects, and strengthen their love for Allah and His Messenger. In addition, the use of digital media supports the expansion of da’wah outreach. The role of Islamic musical arts is proven to enhance students’ religious motivation, as reflected in increased enthusiasm for worship, participation in religious activities, confidence in delivering da’wah, and discipline in practicing Islamic values. Therefore, Islamic musical arts serve as an innovative and relevant da’wah strategy in fostering students’ religious motivation in the Islamic boarding school environment.